Pengembangan Sistem Informasi Masjid Darul Arham Menggunakan Metode V-Model dan UAT (User Acceptance Testing) - Vicky Malik Anjasmara; Arif Hadi Sumitro (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2023)
Darul Arham Mosque is a mosque located in Kunir Hamlet, Singojuruh Village, Singojuruh District, Banyuwangi. Darul Arham Mosque does not yet have an information system in managing data related to mosques. The amount of information and activities at the Darul Arham Mosque, the mosque’s financial management has not yet been organized, the mosque’s data processing is still done manally, making it dificult for mosque administrators to process and convey the contens of the data. To solve this problem, a management system is needed that can be accessed easily , anytime and anywhere by mosque administrators and provides detailed information abaout the Darul Arham Mosque. In this study the authors use the v-model methode and user acceptance testing. It is hoped that this information system can assist mosque administrators un managing data related to the Darul Arham Mosque, as well as assisting the public in finding mosque information through existing website-based information systems